Meningkatkan Hasil Belajar Menggambar Instalasi Pemipaan Air Bersih melalui Metode Perancangan (Project Method) pada Siswa Kelas XI DPIB SMK Negeri 2 Karang Baru - Ridhawanti (Medan Resource Center, 2022)
This Classroom Action Research (CAR) was carried out considering the importance of efforts to improve the quality of learning outcomes through various ways or optimal learning strategies, where the teacher plays a very important role in preparing students to take part in learning. The design method was chosen to improve the learning outcomes of clean water installation drawings in class XI DPIB SMK Negeri 2 Karang Baru Odd Semester TP. 2021/2022. This is deemed very necessary because interest and motivation and student learning outcomes in the class are still low. The subjects of this study amounted to 20 people. The research data was obtained by using a performance test in the form of student design drawings and student observation sheets. From the results of this study, it was revealed that the ability of students to design drawings of clean water piping installations using the design learning method could be improved. The average value of student learning outcomes from cycle I and cycle II continued to increase from 81.75 to 87.90 with 65% of students completing cycle I and cycle II 100%.